FEEDBACK: SOME COMMENTS ON A NON-REVIEW - Freisen, John W. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1975)
Professor Stevenson’s review of Profiles of Canadian Educators comes very close to being a non-review because the criticisms contained therein are lacking in terms of the rigor required of an objective appraisal. I shall support this statement with several examples such as a failure to provide evidence, faulty labelling, and generalizing, and I will show that Mr. Stevenson has scored only one point in his piece and that pertaining to a technical error.